2003
DOI: 10.1136/thorax.58.9.757
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating 92 kDa matrix metalloproteinase (MMP-9) activity in exacerbations of asthma

Abstract: Background: The 72 kDa matrix metalloproteinase 2 (MMP-2) and the 92 kDa matrix metalloproteinase 9 (MMP-9) are type IV collagenases implicated in various aspects of inflammation including accumulation of inflammatory cells, tissue injury, and development of remodelling. The role of these enzymes in the pathogenesis of asthma exacerbations is unknown. Methods: Circulating levels of MMP-2 and MMP-9 proteins and the expression of their inhibitor, tissue inhibitor of metalloproteinase 1 (TIMP-1), were measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 26 publications
5
30
0
10
Order By: Relevance
“…There is strong evidence of MMP-9 involvement in asthma, particularly in patients with severe asthma [39] and in acute, severe exacerbations [40]. MMP-9 is expressed by inflammatory cells and structural cells of the lungs, including the ASM cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence of MMP-9 involvement in asthma, particularly in patients with severe asthma [39] and in acute, severe exacerbations [40]. MMP-9 is expressed by inflammatory cells and structural cells of the lungs, including the ASM cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an increased MMP-9 activity has been reported in patients with allergic asthma. [31][32][33] Allergic bronchial asthma is characterized by upregulation of IgE and Th2 cytokine levels, infiltration of inflammatory cells such as macrophages, neutrophils and eosinophils, and airway hyperresponsiveness (AHR). It has also been reported that the gene expression of MMP-12 was upregulated in patients with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase in both the level of circulating MMP-9 [67] and its activity in BAL fluid [68] was also seen in patients after exacerbation compared with patients with asthma. Additionally, MMP-9 staining in the subepithelial basement membrane region was reportedly higher in severe asthmatic biopsies than in control subjects [69].…”
Section: Increased Deposition Of Extracellular Matrixmentioning
confidence: 99%